Regulation of RHBDD1 in the invasion of esophageal cancer cells via ELK3/Wnt/β-catenin signaling pathway - Xu, Bing; Chen, Hui; Sun, Xinchen; Cheng, Hongyan; Chipusu, Kavimbi; Hua, Wei; Chen, Tingting (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveEsophageal cancer (EC) is one of the most common cancers worldwide. The prognosis for patients with the same stage of EC can vary substantially. Recurrence and metastasis after treatment are still important reasons for poor prognosis of esophageal cancer patients. Rhomboid domain containing 1 (RHBDD1) has been reported to play an important role in the development and progression of various cancers, but its role in esophageal malignancy is poorly understood, and this paper aims to explore the role of RHBDD in esophageal squamous cell carcinoma.MethodologyThis study employed in vitro and in vivo approaches to investigate molecular mechanisms in ESCC. ECA109 cells were cultured in RPMI 1640 with 10% FBS under 5% CO2 at 37°C. RNA extraction (Trizol) and qRT-PCR (SYBR Green, β-actin normalization) were performed in triplicate. Lentiviral shRNA constructs targeting RHBDD1/ELK3 (GenePharma) were transfected, with stable clones selected via puromycin and validated by Western blot/qRT-PCR. Proliferation was assessed via CCK-8 (absorbance at 450 nm) and EdU assays (Ribo-Bio kit), while apoptosis was quantified by annexin V-FITC/PI staining using flow cytometry. Immunofluorescence detected β-catenin localization (Abcam antibodies). For in vivo analysis, BALB/c nude mice (n = 6/group) received subcutaneous ESCC xenografts, monitored biweekly for tumor volume (L × W2/2). IHC evaluated protein expression (Ki67, EMT markers). Data, presented as mean ± SD, were analyzed by Student’s t-test or ANOVA (Dunnett’s post hoc; p < 0.05). Protocols followed institutional ethical guidelines.ResultsRHBDD1 promotes cell invasion and migration in ESCC cells. Furthermore, knockdown of RHBDD1 in ESCC cells reduced lung and liver metastasis in vivo. The results also indicated that RHBDD1 could promote cell proliferation and inhibit cell apoptosis, which may make ESCC cells more aggressive.ConclusionThe present study shows that RHBDD1 is an activator of epithelial-mesenchymal transition. This study contributes to the understanding of the role of RHBDD1 in ESCC patients and serves as a valuable resource for in-depth exploration of the pathogenesis of ESCC and the identification of potential therapeutic targets in the future.